Boosting Stability and Inkjet Printability of Pure-Red CsPb(Br/I)3 Quantum Dots through Dual-Shell Encapsulation for Micro-LED Displays - Wang, Shujian; Chen, Dejian; Xu, Kunyuan; Hu, Jie; Liang, Sisi; He, Kun; Zhu, Haomiao; Hong, Maochun (ACS energy letters, 2024)
The development of pure-red perovskite quantum dots (QDs) for displays is lagging due to their structural instability. Herein, we present a new core dual-shell structure with CsPb(Br/I)3@SiO2@polystyrene (PS) QDs, emitting at 627 nm. The structure consists of a CsPb(Br/I)3 core, an intermediate SiO2 layer, and an outermost PS shell. The PS shell plays a crucial role in silane hydrolysis, preventing SiO2 aggregation and enhancing the dispersibility of the CsPb(Br/I)3@SiO2@PS QDs. These QDs exhibit enhanced resilience against irradiation, moisture, and thermal stress, maintaining approximately 80% of their initial photoluminescence (PL) intensity after 3 days of UV irradiation exposure or after 2 days of being subject to high humidity and temperature conditions. Utilized as red inkjet inks, these QDs enable the inkjet printing of a vivid red dot matrix and a Chinese chess pattern. This innovation holds promise for expanding the practical utilization of CsPb(Br/I)3 QDs, particularly in full-color micro-LED display technology via inkjet printing.